Preferences of Gen Z for Investing in Socially Accountable Funds - Devanshi Dave; Abhishek Parikh (Celebes Scholar pg, 2022)
Socially accountable fund (SAF) in India continues to be a fresh investment approach for its investors and socially accounted business. It is a funding that considers social justice, environmental sustainability, in addition to the incorporation of moral materials of enterprise and trade. This paper tries to determine factors influencing ‘Generation Z`s’ (Gen-Z) preference to invest in socially accountable funds. The ‘Theory of Planned behaviour (TPB)’’ focuses on symbolize attitude, subjective norms, and perceived behavioural management by the investors. These factors are included to take a look at how those variables sequentially affect the adoption of socially accountable funding. More importantly, socially accountable consumption, in addition to perceived ethical duty also are protected making use of growing a prolonged idea of deliberate conduct studies framework. The statistics become amassed thru a survey, using a self-administered questionnaire the usage of a ‘6-factor Likert Scale’ amid 287 respondents in Gujarat. All the hypothesis are supported by the findings, besides for the connection among subjective norms and the adoption of socially accountable funding (SAF). The findings offer beneficial facts to the vendors of funding merchandise and services, in particular in increasing their marketplace in the direction of selling socially accountable funding, especially amongst Gen-Z.